P006 'First test along then together' – the practice of couple's HIV testing in ethiopia. (14th July 2019) - Hailemariam, Tewodros Getachew; Rawstorne, Patrick; Sisay, Mitike; Nathan, Sally
Abstract : Background: Some evidence indicates that Couple HIV Testing & Counselling (CHTC) is an approach that could be used to enable more people to be reached. However, little is known about how couples may use this service and what their concerns are around the approach. This study aimed to understand how individuals who had ever been in a long-term heterosexual relationship intended to use CHTC in Ethiopia and their beliefs about its benefits and potential harms. Methods: A qualitative study was conducted in Addis Ababa, Ethiopia. We interviewed individuals who had ever been in a long-term heterosexual relationship (n=21), and key-informants (n=11) including religious leaders, health-care providers and case managers. The interview data were transcribed verbatim and thematically analysed using NVivo 11. The data were coded to look for concepts and patterns across the interviews, and relevant themes and sub-themes identified which captured key aspects related to individual's views on undertaking HIV-testing with a sexual partner. Results: Most participants regarded CHTC as an important HIV-testing approach for people who are in a long-term heterosexual relationship and expressed the view that there was 'nothing like testing together'. However, many participants said they would prefer to be tested alone to check their own HIV-status before undertaking or deciding to undertake CHTC - 'first alone then together'. This strategy was expressed as a way of managing their concerns about being HIV-positive and 'fear of the consequences' including potential accusations of infidelity, relationship break-up, and potentially exposed in the community as being HIV-positive. Conclusion: The findings of this study suggest that while CHTC has been actively promoted in Ethiopia, people may be concerned about undertaking CHTC without prior individual HIV-testing and have developed ways of making the process work for them. More work is needed to understand the approach couples considering is a more dignified, effective and cost-effective way. Disclosure: No significant relationships.